Transforming ODL through online collboration : the hidden curriculum - Zoraini Wati Abas,; Ansary Ahmed,; Kaur , Kuldip; Hairudin Harun, (2008)
This paper will describe how research on online interactions led to the development of a Collaborative Online Learning (COL) Model at Open University Malaysia (OUM). The model aimed to improve the quality of learning and to develop a set of skills required of graduates today for a K-society. The model also reinforces the development of skills such as analytical, problem-solving, communication and ICT literacy as well as being able to use the latest information technologies to conduct research, identify relevant resources, select the right information, analyse and make presentations, share resources, collaborate and become team players. This “hidden curriculum” is realized through learner engagement in online discussions among course mates. In the discussions, they would be contributing opinions, suggestions, ideas, information based on research while working collaboratively as a team on a particular course-related assignment. The latter could be a specific task, problem, scenario or case study. The paper will also describe an ongoing research on the gradual implementation of the COL model over several semesters.